Maternal Supplementation With Krill Oil During Breastfeeding and Long-Chain Polyunsaturated Fatty Acids (LCPUFAs) Composition of Human Milk: A Feasibility Study - Cimatti, Anna Giulia; Martini, Silvia; Munarini, Alessandra; Zioutas, Maximilano; Vitali, Francesca; Aceti, Arianna; Mantovani, Vilma; Faldella, Giacomo; Corvaglia, Luigi (Frontiers in Pediatrics, 2018)
Background Docosahexaenoic acid (DHA) is a major constituent of neuronal and retinal membranes and plays a crucial role in brain and visual development within the first months of life. Dietary intakes are fundamental to provide neonates with adequate DHA supply; hence, maternal supplementation might represent a useful strategy to implement DHA contents in breast milk (BM), with possible benefits on neonatal neurodevelopment. Antarctic krill is a small crustacean rich in highly available phospholipid-bound DHA. This pilot study aimed to evaluate whether maternal supplementation with krill oil during breastfeeding increases long-chain polyunsaturated fatty acids (LCPUFAs) BM contents. Methods Mothers of infants admitted to the Neonatal Intensive Care Unit were enrolled in this open, randomized-controlled study between 4 and 6 weeks after delivery and randomly allocated in 2 groups. Group 1 received an oral krill oil-based supplement providing 250 mg/day of DHA and 70 mg/day of eicosapentaenoic acid (EPA) for 30 days; group 2 served as control. BM samples from both groups were collected at baseline (T0) and day 30 (T1) and underwent a qualitative analysis of LCPUFAs composition by gas chromatography/mass spectrometry. Results Sixteen breastfeeding women were included. Of these, 8 received krill-oil supplementation and 8 were randomized to the control group. Baseline percentage values of DHA (%DHA), arachidonic acid (%AA) and EPA (%EPA) did not differ between groups. A significant increase in %DHA (T0: median 0.23% [IQR 0.19;0.38], T1:0.42% [0.32;0.49], p 0.012) and %EPA (T0: median 0.10% [IQR 0.04;0.11], T1:0.11% [0.04;0.15], p 0.036) and a significant reduction in %AA (T0: median 0.48% [IQR 0.42;0.75], T1:0.43% [0.38;0.61], p 0.017) between T0 and T1 were shown in Group 1, whereas no difference was observed in Group 2. Consistently, a significant between-group difference was observed in percentage changes from baseline of DHA (∆%DHA, group 1: median 64.2% [IQR 27.5;134.6], group 2: -7.8% [-12.1;-3.13], p 0.025) and EPA (∆%EPA, group 1: median 39% [IQR 15.7;73.4]; group 2: -25.62% [-32.7;-3.4], p 0.035). Conclusions Oral krill oil supplementation effectively increases DHA and EPA contents in BM. Potential benefits of this strategy on brain and visual development in breastfed preterm neonates deserves further evaluation in targeted studies.